Laporan Pengabdian Masyarakat Edukasi Ansietas pada Ibu Hamil dan Ibu Balita di Posyandu Loa Bakung Samarinda - Richa Cahya Setyowati; Shabrina Safitri; Devi Clarisa Amanda; Imellia Harmoni Syahputri; Jihan Aqilah; Fatir Bayu Pratama; Nurjanah Nurjanah; Arief Budiman (Jurnal Informasi Pengabdian Masyarakat, 2026)
The mental health of pregnant women and mothers with toddlers is an important aspect that requires serious attention because physical, psychological, hormonal, and social changes may trigger the emergence of anxiety. Poorly managed anxiety may lead to negative impacts on maternal health, fetal conditions, and child growth and development. This community service activity aimed to improve the knowledge and awareness of pregnant women and mothers with toddlers regarding anxiety, its signs and symptoms, potential impacts, and simple strategies for managing anxiety. The activity was conducted at Posyandu Loa Bakung Samarinda on April 17, 2026, targeting pregnant women and mothers with toddlers. The methods employed included health education sessions, discussions and question-and-answer activities, demonstrations of deep breathing relaxation techniques, and the distribution of educational media in the form of leaflets and posters. Evaluation was carried out verbally to assess participants’ level of understanding after the activity. The results demonstrated that most participants were able to understand the concept of anxiety, identify its signs and symptoms, comprehend its effects on maternal and child health, and practice simple techniques to reduce anxiety. Furthermore, the activity increased participants’ awareness of the importance of maintaining mental health during pregnancy and child-rearing periods. Therefore, mental health education through posyandu activities can serve as a promotive and preventive effort to improve the quality of maternal and child health within the community.